Primary endobronchial myxoid leiomyoma in a child: An unusual case report and review of literature - Ashutosh Awasthi; Suparna Dubey; Abha K Sabhikhi; Sabyasachi Bal (Wolters Kluwer Medknow Publications, 2016)
Primary leiomyomas are rare benign tumors of the lung and only 25 cases have been documented in children, most of which are endobronchial. Leiomyomas are benign smooth muscle neoplasms, usually diagnosed on morphological characteristics. However, immunohistochemistry plays a crucial role in the lineage differentiation when these are encountered at unusual sites or with unexpected morphological features. We report a case of endobronchial tumor of a 13-year-old male child who presented with a dry cough and hemoptysis. A mass lesion in the right main bronchus was detected by bronchoscopy and contrast-enhanced computed tomography. On histopathological examination of the resected specimen, a diagnosis of myxoid leiomyoma was made. To the best of our knowledge, this is the first case of myxoid leiomyoma to be reported in the respiratory tract. This case also demonstrates the need for a high index of suspicion and the role of immunomarkers in the diagnosis of such challenging cases.